Regulation of gut microbiota: a novel pretreatment for complications in patients who have undergone kidney transplantation - Ye, Jiajia; Yao, Junxia; He, Fangfang; Sun, Jing; Zhao, Zheng; Wang, Yumei (Frontiers in Cellular and Infection Microbiology, 2023)
Kidney transplantation is an effective method to improve the condition of patients with end-stage renal disease. The gut microbiota significantly affects the immune system and can be used as an influencing factor to change the prognoses of patients who have undergone kidney transplantation. Recipients after kidney transplantation showed a lower abundance of Firmicutes and Faecalibacterium prausnitzii and a higher proportion of Bacteroidetes and Proteobacteria. After using prebiotics, synbiotics, and fecal microbiota transplantation to regulate the microbial community, the prognoses of patients who underwent kidney transplantation evidently improved. We aimed to determine the relationship between gut microbiota and various postoperative complications inpatients who have undergone kidney transplantation in recent years and to explore how gut microecology affects post-transplant complications. An in-depth understanding of the specific functions of gut microbiota and identification of the actual pathogenic flora during complications in patients undergoing kidney transplantation can help physicians develop strategies to restore the normal intestinal microbiome of transplant patients to maximize their survival and improve their quality of life.